Unveiling the Hidden Bat Diversity of a Neotropical Montane Forest - Chaverri Echandi, Gloriana (2016)
Mountain environments, characterized by high levels of endemism, are at risk of experiencing significant biodiversity loss due to current trends in global warming. While many acknowledge their importance and vulnerability, these ecosystems still remain poorly studied, particularly for taxa that are difficult to sample such as bats. Aiming to estimate the amount of cryptic diversity among bats of a Neotropical montane cloud forest in Talamanca Range—south-east Central America—, we performed a 15-night sampling campaign, which resulted in 90 captured bats belonging to 8 species. We sequenced their mitochondrial cytochrome c oxidase subunit I (COI) and screened their inter- and intraspecific genetic variation. Phylogenetic relations with conspecifics and closely related species from other geographic regions were established using Maximum Likelihood and Bayesian inference methods, as well as median-joining haplotype networks. Mitochondrial lineages highly divergent from hitherto characterized populations (> 9% COI dissimilarity) were found in Myotis oxyotus and Hylonycteris underwoodi. Sturnira burtonlimi and M. keaysi also showed distinct mitochondrial structure with sibling species and/or populations. These results suggest that mountains in the region hold a high degree of endemicity potential that has previously been ignored in bats. They also warn of the high extinction risk montane bats may be facing due to climatic change, particularly in isolated mountain systems like Talamanca Range.